The Influence of Influencers and Brand Awareness on Interest in Buying Samyang Brand Instant Noodles in Surabaya - Yusuf Argyanto; Nurini Ika Kusuma (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research aims to analyze the influence of influencers and brand awareness on interest in buying Samyang brand instant noodles in Surabaya. Based on the results of research on 100 respondents, influencers and brand awareness have a positive and significant effect on interest in buying Samyang brand instant noodles. The encouragement variable from influencers is the most significant factor in influencing consumer buying interest, while the most influential indicator of the brand awareness variable is brand use or consumption. In this context, influencers and brand awareness are important factors in promoting and influencing consumer purchasing interest in Samyang brand instant noodle products. This research is in line with previous research which shows the positive and significant influence of social media influencers and brand awareness on interest in purchasing products.